2015
DOI: 10.1007/s11302-015-9467-2
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine suppresses recombinant human P2X7 responses

Abstract: P2X7 receptor (P2X7) activity may link inflammation to depressive disorders. Genetic variants of human P2X7 have been linked with major depression and bipolar disorders, and the P2X7 knockout mouse has been shown to exhibit antidepressive-like behaviour. P2X7 is an ATP-gated ion channel and is a major regulator of the pro-inflammatory cytokine interleukin 1β (IL-1β) secretion from monocytes and microglia. We hypothesised that antidepressants may elicit their mood enhancing effects in part via modulating P2X7 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…The above discussion further raises another important question relating to the implication of P2X7R and microglia activation in the effect of EA and other antidepressants. A previous study in which trifluoperazine and paroxetine suppressed P2X7-mediated IL-1β secretion from lipopolysaccharide (LPS)-primed human CD14+ monocytes has shed some light on the question (Dao-Ung et al, 2015 ). In addition, our previous research has confirmed that knockout P2X7R (P2X7-null or P2X7–/– mice) displayed an antidepressant phenotype after exposure to CUS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above discussion further raises another important question relating to the implication of P2X7R and microglia activation in the effect of EA and other antidepressants. A previous study in which trifluoperazine and paroxetine suppressed P2X7-mediated IL-1β secretion from lipopolysaccharide (LPS)-primed human CD14+ monocytes has shed some light on the question (Dao-Ung et al, 2015 ). In addition, our previous research has confirmed that knockout P2X7R (P2X7-null or P2X7–/– mice) displayed an antidepressant phenotype after exposure to CUS.…”
Section: Discussionmentioning
confidence: 99%
“…The pro-inflammatory cytokines are suggested to be involved in the pathophysiology of MDD (Yirmiya et al, 2000 ; Dantzer et al, 2008 ; Song and Wang, 2011 ; Eyre and Baune, 2012 ). The activation of microglia may have detrimental effects on neurons by expressing and synthesizing pro-inflammatory cytokines such as IL-1β, which induces neuro-inflammation and eventually induces the death of neurons under these conditions (Brown and Vilalta, 2015 ; Dao-Ung et al, 2015 ). In our present study, we showed that CUS induced the dramatic activation of microglia, which was in accordance with the previous studies indicating that diversiform stress including: environmental, psychological and chronic stress activated microglia (Hinwood et al, 2012 ; Liu et al, 2015 ; McKim et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at the concentration range eliciting P2X4R inhibition, duloxetine had no effect on P2X7R. This is in contrast to paroxetine which also inhibits P2X7R [ 13 , 31 ]. The tricyclic antidepressant amitriptyline has been reported to inhibit rat and mouse, but not human P2X4R [ 21 ]; in this study, the inhibitory effect of duloxetine was observed in rodent and human P2X4R, indicating the inhibition is not restricted to a specific species.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation contributes to psychiatric and neurological diseases (e.g., depressive disorders, mania, obsessive-compulsive disorder (OCD) and neuropathic pain) (Dao-Ung et al, 2015). Cytokines, such as IL-1β, IL-6 and TNF-α, and reactive oxygen species are released from microglia following P2X7 receptor activation (He et al, 2017;Fernandes et al, 2016), suggesting a link between the pro-inflammatory actions of P2X7 and CNS diseases.…”
Section: Introductionmentioning
confidence: 99%